Translatome of dorsal striatum parvalbumin interneurons revisited: insights across diverse experimental paradigms - Naon, Claire; Castell, Laia; Thirard, Steeve; Moreno, Maria; Rialle, Stéphanie; Goetz, Eva; Casals, Eloi; Rogliardo, Angelina; Gut, Marta; Esteve-Codina, Anna; Quintana, Albert; Bertaso, Federica; et al. (Frontiers in Cellular Neuroscience, 2025)
Parvalbumin (PV) interneurons in the dorsal striatum (DS) are fast-spiking GABAergic cells critical for feedforward inhibition and synaptic integration within basal ganglia circuits. Despite their well-characterized electrophysiological roles, their molecular identity remains incompletely defined. Using the Ribotag approach in Pvalb-Cre mice, we profiled the translatome of DS PV interneurons and identified over 2,700 transcripts significantly enriched (fold-change > 1.5) in this population. Our data validate established PV markers and reveal a distinct molecular signature of DS PV neurons compared to PV interneurons from the nucleus accumbens. Gene ontology analyses highlight prominent expression of genes related to extracellular matrix components, cell adhesion molecules, synaptic organization, ion channels, and neurotransmitter receptors, particularly those mediating glutamatergic and GABAergic signaling. Notably, perineuronal net markers were robustly expressed in DS PV interneurons and confirmed by immunofluorescence. Transcriptomic analysis of DS PV neurons following repeated d-amphetamine exposure identified Gm20683 as the only differentially expressed transcript between treated groups. Furthermore, RNAseq analysis of mice subjected to an operant behavior paradigm with two types of food reward (high-palatable diet or standard chow) identified over 1,000 and 100 genes enriched in DS PV neurons from standard and high-palatable masters, respectively. These findings provide a comprehensive molecular profile of DS PV interneurons, distinguishing them from other striatal PV populations, and reveal specific gene expression changes associated with psychostimulant exposure and reward-driven behaviors. Our findings deepen insight into the molecular mechanisms of PV interneuron activity in striatal circuits and their potential roles in neuropsychiatric, motor and reward-related disorders.